The characters of the traditional residence of Sasak tribe based on sikut awak: An ethnomathematics study - Lalu Muhammad Fauzi; Muhammad Gazali (Universitas Hamzanwadi, 2022)
In cultural anthropology, people have recognized various mathematical activities, such as counting, calculating, measuring, and weighting, with different terms derived from each culture. Community activities in responding to the existence of their environment will give rise to mathematics as part of problem-solving, including finding characters or features of residence to build. Therefore, this study explores mathematical forms in the measurement of residential characters based on sikut awak that can be used in mathematics learning. This research is an ethnographic study. Data were collected from various literature studies, field observations, and interviews. Informants included in the study were two cultural experts, one Adat leader, and one traditional builder who knows sikut awak’s measurement format in determining the traditional residential characters of Sasak people. This study shows that the determination of residential characters uses mathematical models in its calculation.